Detection of florfenicol resistance in opportunistic Acinetobacter spp. infections in rural Thailand - Tan, Bernice Siu Yan; Mohan, Lalit; Watthanaworawit, Wanitda; Ngamprasertchai, Thundon; Nosten, Francois H.; Ling, Clare; Bifani, Pablo (Frontiers in Microbiology, 2024)
Florfenicol (Ff) is an antimicrobial agent belonging to the class amphenicol used for the treatment of bacterial infections in livestock, poultry, and aquaculture (animal farming). It inhibits protein synthesis. Ff is an analog of another amphenicol, chloramphenicol used for the treatment of human infections on the WHO essential medicine list. Due to the extensive usage of florfenicol in animal farming, there has been a surge in the spread of resistance amongst zoonotic pathogens. Horizontal gene transfer (HGT) plays an important role in the transfer of resistance genes and associated gene cassettes amongst the same and different species of bacteria. There are numerous reports of resistance genes from organisms infecting or colonizing animals found in human pathogens, suggesting possible genetic exchange between human and zoonotic pathogens. One of these is floR, a gene that encodes for an efflux pump that removes Ff from bacterial cells conferring resistance against amphenicol and often associated with mobile genetic elements and other resistant determinants. Here, we report the presence of a conserved floR gene in unrelated Acinetobacter spp. isolated from human bacterial infections and environmental samples in rural Thailand, suggesting multiple and independent inter-species genetic exchange of drugresistant determinants. In this study, floR was found to be in the variable region containing various mobile genetic elements along with the presence of other antibiotic resistance determinants; however, no evidence of HGT could be determined. The floR gene identified in this study is chromosomal and not encoded on plasmids as shown in some previous studies. The study highlights the plausible impact of antimicrobials used in veterinary settings on human health. Florfenicol shares cross-resistance with chloramphenicol which is still in use in several countries. Furthermore, by selecting for floR-resistance genes we may be selecting and facilitating the zoonotic and reverse zoonotic exchange of other flanking resistance markers between human and animal pathogens or commensals with detrimental public health consequences.